Transparencia de gestión y valor público en la Municipalidad Provincial de Requena 2024 - Acosta Pinedo, Jovino (2025)
The present study aimed to determine the relationship between management transparency and public value in the Provincial Municipality of Requena 2024. This was a basic, descriptive-correlational research project with a non experimental design. For data collection, the study population consisted of 382 residents of the town. The results revealed that transparency in municipal management was rated as average by 38% of citizens. This perception was supported by the fact that the municipality occasionally provided timely information when requested by citizens. It was also observed that it only occasionally offered the accessible means, both in person and online, necessary to access public information. Public value, on the other hand, was rated average by 40%. This result was explained by the fact that citizens were only occasionally satisfied with the security services offered by the municipality. However, it was noted that, on almost all occasions, the municipality carried out public works that significantly contributed to improving local infrastructure. Finally, the statistical analysis determined a moderate positive correlation (r=0.585) between management transparency and public value in the Provincial Municipality of Requena for the year 2024. Similarly, a moderate correlation (r=0.404) was identified between the management of access to information requests and public value; a moderate relationship (r=0.503) between the proactive publication of information and public value; and a moderate positive correlation (r=0.537) between the practice of accountability and the increase in public value. All of these relationships were statistically significant (p=0.000), confirming the existence of a link between these variables in the context evaluated.